Pengaruh Dana Zakat, Infak, Shodaqoh, Obligasi Syariah Dan Reksadana Syariah Terhadap Pertumbuhan Ekonomi - Elisa, Elisa; Zamzami, R. Mohd (CV RIFAINSTITUT, 2022)
This study aims to analyze the effect of zakat funds, infaq/shadaqoh (ZIS), Islamic bonds (sukuk), Islamic mutual funds on economic growth for the period 2011 – 2020. This type of research is a quantitative research using multiple linear regression analysis as data analysis, and using secondary data in the form of time series. The data used is quarterly data from zakat funds, infaq/shadaqoh (ZIS), sharia bonds (sukuk), sharia mutual funds and gross domestic product (GDP) in 2011 – 2020. The data obtained is then processed using Eviews 10. Based on the results This study shows that partially zakat funds, infaq/shadaqoh (ZIS) have a positive and insignificant effect on economic growth. Then, Islamic bonds (sukuk) have a positive and significant effect on economic growth. And the variable of Islamic mutual funds has a negative and significant effect on economic growth. Simultaneously, zakat funds, infaq/shadaqoh (ZIS), Islamic bonds (sukuk), Syariah Mutual funds have a positive and significant effect on economic growth. that the Adjusted R – Squared value shows a result of 0.698119 or 69.81%. This means that the variables of zakat, infaq/shodaqoh, sukuk, and sharia mutual funds have an effect of 69.81% on economic growth. While the rest is influenced by other variables not mentioned in this study